2004
DOI: 10.1016/j.ijimpeng.2003.08.007
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of impulse-resistant metal sandwich plates

Abstract: The performance of metal sandwich plates under impulsive blast loads is compared to that of solid plates made of the same material and having the same weight. Three core geometries are considered: pyramidal truss, square honeycomb and folded plate. Plates of infinite length and clamped along their sides are subject to uniform impulsive load. The momentum impulse is applied to the face sheet towards the blast in the case of the sandwich plate, while it is distributed uniformly through the thickness of the solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
288
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 479 publications
(299 citation statements)
references
References 7 publications
10
288
0
1
Order By: Relevance
“…Recent experiments have shown that the back face deflections of centrally loaded edge clamped sandwich panels can be significantly less than equivalent areal density solid plates subjected to the same loading [3][4][5][6][7][8]. Theoretical assessments indicate this beneficial effect arises from two phenomena: a reduction in the impulse acquired by the sandwich panel front face as a result of a fluid-structure interaction (FSI) effect [3,4,[8][9][10] and the higher flexural stiffness and strength of the sandwich.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent experiments have shown that the back face deflections of centrally loaded edge clamped sandwich panels can be significantly less than equivalent areal density solid plates subjected to the same loading [3][4][5][6][7][8]. Theoretical assessments indicate this beneficial effect arises from two phenomena: a reduction in the impulse acquired by the sandwich panel front face as a result of a fluid-structure interaction (FSI) effect [3,4,[8][9][10] and the higher flexural stiffness and strength of the sandwich.…”
Section: Introductionmentioning
confidence: 99%
“…After the beneficial FSI effect had been confirmed in water [2][3][4][5][6][7][8], numerous sandwich panel concepts for impulse and pressure mitigation have been explored [7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, attention has been paid to the potential use of sandwich plates in this protective role. Fleck and Deshpande [1] and Xue and Hutchinson [2] have argued that an underwater blast imparts a lower momentum to sandwich plates than monolithic plates of equal mass. The reduced momentum is associated with the earlier onset of cavitation in the water for sandwich plates with a light front face sheet and a deformable core.…”
Section: Introductionmentioning
confidence: 99%
“…A fundamental issue with the inherent brittleness of these systems is that although they perform well when the structures deform in their elastic regime, they tend to fail catastrophically when a specific level of impact momentum is reached [9]. In contrast, metals show a more benign transition at increased levels of impact momentum due their ability to deform plastically [11]. The chief disadvantage with metal alloys is their high density; this necessitates that the structures become very thin walled and buckling dominated structures at low areal densities.…”
Section: Introductionmentioning
confidence: 99%